Analysis of the Role of BPRS Mitra Harmoni Islamic Bank in Improving Community Welfare through Ball Pick-Up Financing in the Production of Clay Go International - Rosyid, Wildan; Eda Yuda, Santra; Nurwahidah, Ana (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Islamic banks have emerged as one of the key pillars of Indonesia’s financial system, providing not only financial services but also contributing to social welfare in line with sharia principles. Among them, BPRS Mitra Harmoni Malang has introduced an innovative Jemput Bola (ball pick-up) savings and financing programme designed to overcome barriers to financial access and to promote community empowerment. This study aims to analyse the role of the Jemput Bola programme in enhancing community welfare and financial inclusion within the framework of maqashid sharia. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis conducted between January and February 2025. The findings reveal that the Jemput Bola system significantly reduced access barriers for low-income and informal sector communities, increased participation in savings and financing products, and fostered microenterprise development, particularly in sectors such as clay crafts, food production, and retail trade. The programme also improved public trust in Islamic banking by emphasizing transparency, ethical practices, and the avoidance of riba. Overall, the study demonstrates that BPRS Mitra Harmoni’s Jemput Bola programme is more than a marketing innovation; it is a strategic model for inclusive growth and community welfare improvement. By aligning with maqashid sharia objectives (hifz al-mal, hifz an-nafs, and hifz al-nasl) the programme contributes to financial stability, socio-economic empowerment, and sustainable development. These results suggest that the model has strong potential for replication by other Islamic rural banks to strengthen financial inclusion and reduce poverty across Indonesia.